ANALISIS KEKERABATAN MORFOLOGI MANGIFERA DARI SUMATERA TENGAH - Fitmawati Fitmawati; Anggi Swita; Nery Sofyanti; Herman Herman (PTTI, 2013)
Ten distinct species of Mangifera were determined in central of Sumatera. This study aimed to characterize and to determine species of Mangifera based on the morphological character. The study had been conducted from December 2012 to March 2013 on 4 study sites in Riau Province by using a survey method and a direct observation. Fifty morphological characters were scored and analyzed using PAUP 4.0. The cladogram formed two main clades, clade I only consisted of M. kemanga and clade II consisted of M. foetida, M. odorata, M. indica, M. laurina, M. sumatrana, M. zeylenica, M. quadrifida, M. torquendra and Mangifera sp. The clustering results in two cladograms were mainly based on the the similarity of morphological characters dan based on the line of evolution.